2020
DOI: 10.3762/bjnano.11.61
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonal boron nitride: a review of the emerging material platform for single-photon sources and the spin–photon interface

Abstract: Single-photon sources and their optical spin readout are at the core of applications in quantum communication, quantum computation, and quantum sensing. Their integration in photonic structures such as photonic crystals, microdisks, microring resonators, and nanopillars is essential for their deployment in quantum technologies. While there are currently only two material platforms (diamond and silicon carbide) with proven single-photon emission from the visible to infrared, a quantum spin–photon interface, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 175 publications
(261 reference statements)
0
56
0
3
Order By: Relevance
“…Different from the two-order nonlinear optical properties, the third-order nonlinear effects exist in any material, including third-harmonic, optical Kerr effect, four-wave mixing, saturated absorption, etc. [153] Taking BP as an instance, Youngblood et al reported its third-harmonic generation (THG) and measure 𝜒 (3) experimentally for the first time. [154] The THG intensity exhibits a fourfold and twofold reliance on the polarization angle when the incident light is polarized along the x-and y-axis, respectively (Figure 7g).…”
Section: Nonlinear Optical Responsementioning
confidence: 99%
“…Different from the two-order nonlinear optical properties, the third-order nonlinear effects exist in any material, including third-harmonic, optical Kerr effect, four-wave mixing, saturated absorption, etc. [153] Taking BP as an instance, Youngblood et al reported its third-harmonic generation (THG) and measure 𝜒 (3) experimentally for the first time. [154] The THG intensity exhibits a fourfold and twofold reliance on the polarization angle when the incident light is polarized along the x-and y-axis, respectively (Figure 7g).…”
Section: Nonlinear Optical Responsementioning
confidence: 99%
“…Candidates include defects in semiconducting transition metal dichalcogenides (TMDs) (for example WSe 2 ) and hexagonal boron nitride (hBN) single crystals [186]. While TMDs require low temperatures for efficient single photon emission, hBN defect centres have been shown to be chemically and thermally stable sources of bright single photon emission, at room temperature [187][188][189].…”
Section: Hexagonal Boron Nitride Defectsmentioning
confidence: 99%
“…109 A laser magnetometer could achieve a very high contrast for the NV ODMR and prompt more practical applications of MRI using bulk diamond. STED has been applied to the study of a group of quantum emitters in 2D hBN, which presents a large variety of SP emission 110,111 from the UV to the NIR. These emitters have been recently identified as carbon related, 24 specifically a carbon-nitrogen substitution with boron vacancies.…”
Section: Stimulated Emission Depletion Microscopymentioning
confidence: 99%